Whole genome sequencing revealed high proportions of ST152 MRSA among clinical Staphylococcus aureus isolates from ten hospitals in Ghana - Beverly Egyir; Christian Owusu-Nyantakyi; Alfred Bortey; Grebstad Rabbi Amuasi; Felicia Amoa Owusu; William Boateng; Hawawu Ahmed; Justice Kwesi Danso; Agnes Akosua Gyamaah Oclu; Quaneeta Mohktar; Georgina Tetteh-Ocloo; Harold Amegbletor; et al. (mSphere)
ABSTRACT Previous studies in Ghana indicated low prevalence of methicillin-resistant Staphylococcus aureus (MRSA) and predominance of ST152 methicillin-susceptible S. aureus (MSSA) among clinical isolates. ST152 MRSA clones are associated with severe infections and epidemics. Using whole genome sequencing (WGS), 159 S. aureus isolated from clinical sources (wound, blood, urine, ear, abscess, umbilical cord, eye, vaginal samples, and others) from 10 hospitals across Ghana were investigated. mecA (gene for methicillin resistance) was detected in 38% of the isolates. Panton–Valentine leucocidin toxin (PVL) gene occurred in 65% isolates, with 84% of the MRSA’s harboring the PVL gene. ST152 was the major clone, with 74% harboring the mecA gene. Other MRSA clones detected were ST5, ST5204, ST852, and ST1. MSSA clones included ST3249, ST152, ST5, ST1, and ST8. Twenty-three genes encoding resistance to 12 antimicrobial classes were observed with blaZ (97%) being the most prevalent. Other predominant resistance genes included tetK (46%), cat (42%), and dfrG (36%) encoding resistance for tetracyclines, phenicols, and diaminopyrimidine, respectively. Virulence genes for enterotoxins, biofilms, toxic-shock-syndrome toxins, hemolysins, and leukotoxins were also detected. Phylogenetic analysis revealed a shift in the dominant clone from MSSA ST152 to MRSA ST152 over the past decade. The study provides valuable insights into the genomic content of S. aureus from clinical sources in Ghana. The finding of ST152 MRSA in high numbers suggests a shifting epidemiological landscape of these pathogens and continuous surveillance using robust tools like WGS is needed to monitor the rise and spread of these epidemic clones in the country.IMPORTANCESince its emergence in 1959, MRSA has been a significant public health concern, causing infections in both clinical and community settings. Patients with MRSA-related infections experience higher mortality rates due to its ability to evade antimicrobials and immune defenses. In Ghana, understanding the molecular epidemiology of MRSA has been hindered by the lack of appropriate laboratory infrastructure and the limited capacity for molecular data analysis. This study, the largest genomic study of S. aureus in Ghana, addresses this gap by utilizing whole genome sequencing to examine the diversity of circulating S. aureus strains from 10 hospitals. Our findings highlight the predominance of pandemic clones, particularly ST152, and the notable transition of ST152 MSSA to ST152 MRSA over the past decade. The findings from this study supports AMR surveillance efforts in Ghana and emphasize the importance of implementing genomic surveillance using WGS to comprehensively monitor the rise and spread of multi-drug-resitant organisms such as MRSA in the country.